2020
DOI: 10.1097/prs.0000000000007326
|View full text |Cite
|
Sign up to set email alerts
|

Acute Postoperative Complications in Prepectoral versus Subpectoral Reconstruction following Nipple-Sparing Mastectomy

Abstract: Background: Nipple-sparing mastectomy is associated with improved aesthetics and oncologic safety. Recently, there has been a resurgence in prepectoral reconstruction. Because of limited data comparing complication rates on patients undergoing prepectoral breast reconstruction, this study compared 30-day postoperative complications by plane of prosthetic placement. Methods: A retrospective review was conducted on all consecutive patients undergoing nipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 25 publications
3
36
1
Order By: Relevance
“…Other complications were reported by one NRCS each. Avila et al 15 reported lower analgesic use with prepectoral implants ( P = 0.03; no adjusted effect size reported). Avila et al 15 also reported comparable risk of unplanned repeat surgeries for revision ( P = NS), although no adjusted effect size was reported.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Other complications were reported by one NRCS each. Avila et al 15 reported lower analgesic use with prepectoral implants ( P = 0.03; no adjusted effect size reported). Avila et al 15 also reported comparable risk of unplanned repeat surgeries for revision ( P = NS), although no adjusted effect size was reported.…”
Section: Resultsmentioning
confidence: 96%
“…Avila et al 15 reported lower analgesic use with prepectoral implants ( P = 0.03; no adjusted effect size reported). Avila et al 15 also reported comparable risk of unplanned repeat surgeries for revision ( P = NS), although no adjusted effect size was reported. Nealon et al 37 reported comparable risks of necrosis (adjOR = 1.01, 95% CI 0.74–5.95), explantation (adjOR = 1.01, 95% CI 0.07 to 14.1), capsular contracture (adjOR = 0.30, 95% CI 0.03 to 1.55), and seroma (adjOR = 1.49, 95% CI 0.37–6.11).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“… 58 , 59 Thus, these techniques cannot be assessed in this trial, and the results’ applicability to such techniques is uncertain. According to recent studies, 60 , 61 , 62 , 63 , 64 , 65 , 66 however, the prepectoral position (which, in principle, always includes some type of mesh) renders no higher SSI rates compared with the subpectoral position, so multiple-dose antibiotic prophylaxis is probably not indicated.…”
Section: Discussionmentioning
confidence: 99%